An Exploration into Direct Nature Experiences (DNE) and Biodiversity Knowledge Amongst Island Children : Research Article - Abdullah, Faruhana; Ishak , Nor Asniza; Ahmad, Mohammad Zohir (Journal of Turkish Science Education, 2022)
Children worldwide are increasingly deprived of direct nature experiences. Often rooted in restrictions of urbanization and modernization, this loss may hamper biodiversity conservation through an erosion of biodiversity knowledge. Yet, the extent of this phenomenon in small cities, particularly in rapidly developing islands remain understudied. This study aimed to compare the frequencies of direct nature experiences based on island environments (islands) and evaluate the influences of islands and frequency of direct nature experiences on biodiversity knowledge among children. The sample consisted of 429, 11-12 year-old public-school children from seven islands. Findings of this online survey questionnaire show that the frequency of nature experiences are significantly different based islands but biodiversity knowledge was not. Increased frequency of nature experiences have a positive effect on biodiversity knowledge. Children are better at identifying animals than plants. Hence, meaningful nature experiences must be facilitated to promote biodiversity knowledge.